Epidemiology of syphilis in pregnant women and congenital syphilis in Belarus - Pankratov, Oleg V. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
In Belarus the spread of syphilis has been on the increase since 1988, and theincidence reached its peak in 1996 with 209.7 cases per 100000 inhabitants.During the following years the incidence has reduced, but still remains high with 41 cases in 2004. In the years 1996-2004 all together 4239 pregnant women infected with syphilis were registered in DermatovenereologicalDispensaries in Belarus, giving birth to 116 children with congenital syphilis. The social end economic background of these events is reviewed.
Keywords: Belorusija; Byelarus; epidemiologija; Epidemiology; human pregnancy; nosečnice; nosečnost; Nosečnost, komplikacije infekcijske; Pregnancy Complications, Infectious; Sifilis; Sifilis prirojeni; Syphilis; Syphilis, Congenital